Trust, Morality, and the Privatization of Water Services in Developing Countries. (December 2013) - Rahaman, Abu Shiraz; Everett, Jeff; Neu, Dean
Abstract This article examines the business of water privatization and the ethics implied in the transformation of the water services sector in developing countries. Drawing on data derived from field visits and semi‐structured interviews held with members of government, nongovernmental organizations, and other stakeholders in one country undergoing transformation in this sector, Ghana, the article considers the ethical perspectives of the various involved stakeholders. The analysis draws on three perspectives—Gilligan's ethic of care, Rawls' principles of justice, and virtue ethics—which together highlight the economic, class, and gender‐based dimensions of the privatization debate. Finding that endemic mistrust characterizes this debate, the article considers what is needed to re‐instill trust among stakeholders. Specific implications are provided for business leaders and government policymakers.